Comparison between cognitive, behavioral and cognitive-behavioral approaches in the treatment of panic disorder (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Cognitive-behavioral therapy is the most studied psychotherapeutic modality in panic disorder (PD) and has demonstrated, in the most different experimental studies, to be sufficiently efficient when compared with control groups, psychopharmacological treatments and other forms of unstructured psychotherapies. Literature on the cognitivebehavioral treatment of PD contemplates comparisons between the most used techniques. OBJECTIVES: Revise the literature that compares the effectiveness of the cognitive, behavioral and cognitive-behavioral approaches of PD, detaching the referring limitations to these psychological treatments and the applied research methodologies. METHODS: Literature systematic review, mainly revised in PubMed database. RESULTS: The effectiveness of the cognitive and behavioral interventions and its combination were equalized and hypotheses to this respect have been raised. DISCUSSION: We should attempt to improve important methodological aspects aiming at results even more trustworthy, pointing out directions to contribute to the refinement of the used techniques.